PENDAMPINGAN PENYUSUNAN LAPORAN PENELITIAN TINDAKAN KELAS BAGI GURU DI SMA - Stefanus Notan Tupen; Sofia Sa'o; Gregorius Taga; Konstantinus Denny Pareira Meke; Lely Suryani (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2020)
This assistance aims to improve the understanding and ability of mathematics teachers at SMA Negeri 1 Larantuka regarding the preparation of Classroom Action Research (CAR) reports. Besides, this assistance aims to assist in the preparation and implementation of CAR by assist teachers in its application. The stages carried out in this service are finding the right model to be applied to the learning process, assistance in making proposals, designing learning tools, teacher research activities in class, and compiling reports on the results of CAR. The results are an increase in the understanding and ability of teachers about the implementation of CAR activities. The results are using as input for teachers to improve teacher professional competence by conducting CAR.